Surface proteins of Shiga toxin-producing Escherichia coli mediate association with milk fat globules in raw milk - Bagel, Arthur; Bouvier-Crozier, Marion; Canizares, Mélissa; Hamadou, Badis; Courcol, Louise; Lopez, Christelle; Michel, Valérie; Douellou, Thomas; Sergentet, Delphine (Frontiers in Microbiology, 2023)
By adhering to host cells and colonizing tissues, bacterial pathogens can successfully establish infection. Adhesion is considered the first step of the infection process and bacterial adhesion to anti-adhesive compounds is now seen as a promising strategy to prevent infectious diseases. Among the natural sources of anti-adhesive molecules, the membrane of milk fat globules (MFGs) is of interest because of its compositional diversity of proteins and glycoconjugates. However, few studies have focused on the bacterial molecules involved in MFG-mediated inhibition of bacterial adhesion to enterocytes. In this context, we used three pathogenic Shiga toxin-producing Escherichia coli (STEC) strains (O26:H11 str. 21765, O157:H7 str. EDL933, and O103:H3 str. PMK5) as models to evaluate whether STEC surface proteins are involved in the affinity of STEC for MFG membrane proteins (MFGMPs). The affinity of STEC for MFGMPs was assessed both indirectly by a natural raw milk creaming test and directly by an adhesion test. We found that free STEC surface proteins inhibit the concentration of the pathogen in the MFG-enriched cream in a strain-dependent manner. Moreover, the OmpA and FliC proteins were identified within the protein fraction of MFGMs. Our results suggest that FliC protein participates in STEC adhesion to MFGMPs but other STEC molecules may also participate. Overall, this study highlighted, for the first time, the involvement of STEC surface proteins in the affinity for MFGs. The mechanism of STEC-MFG association is still not fully understood but our results confirm the existence of receptor/ligand type interactions between the bacteria and MFGs. Further studies are needed to identify and specify the molecules involved in this interaction. These studies should take into account the likely involvement of several factors, including adhesion molecules, and the diversity of each STEC strain.